Effect of some environmental conditions on the growth of rhizobium species (Journal of Bio-Science, 2019)
Rhizobium species are involved in symbiotic relationship which can be exploited in agriculture to enhance crop and pasture growth without the addition of nitrogen fertilizers. However, a number of environmental factors are known to affect the symbiotic efficiency of Rhizobium. This current study evaluated tolerance of Rhizobium species isolated from root nodules of cowpea obtained from Akure, Nigeria to variation in temperature, pH levels, salt concentrations, heavy metals as well as antibiotics. Three Rhizobium species were isolated from root nodules of Vignaunguiculata and Phaseolus vulgaris after 34 days of planting yeast extract mannitol agar (YEMA). Their tolerance to environmental factors such as temperature, pH, sodium chloride, heavy metals as well as antibiotics was determined. All the isolates grew very well at 28oC, moderately at 37oC but their growth was hampered at 50o C. Maximal growth was observed at neutral pH. However, Sinorhizobium sp showed high tolerance to pH 7.0. Also, the isolates showed high tolerance to low concentration of sodium chloride (0.1%) and heavy metals with reduction in their optical density at higher concentrations. Rhizobium sp showed high level of tolerance at 4% compared to Mesorhizobium sp. and Sinorhizobium sp. Rhizobium spp. showed resistance to all the antibiotics investigated while Mesorhizobium sp. was sensitive to only to pefloxacin and sparfloxacin, while Sinorhizobium sp. was only sensitive to pefloxacin. The isolates in this study can be assessed for their suitability as inoculants forcowpea in soils below temperature 50oC and at neutral pH.J. bio-sci. 26: 15-24, 2018